2023
DOI: 10.1177/17562848231170947
|View full text |Cite
|
Sign up to set email alerts
|

Early transmural healing and its predictors assessed by magnetic resonance enterography in patients with Crohn’s disease receiving ustekinumab

Abstract: Background: Transmural healing (TH) is a potential therapeutic goal of Crohn’s disease (CD) and is associated with better clinical outcomes. However, few studies have described early TH and its predictors. Objectives: We aimed to evaluate early TH and its predictors using magnetic resonance enterography (MRE) in patients with CD receiving ustekinumab (UST). Design: This was a retrospective observational study. Methods: Patients with active CD treated with UST and their intestinal segments with bowel wall thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…TH was defined as having a bowel wall thickness ≤ 3 mm without any signs of inflammation at week 26. The subgroup of patients who reached TH, compared with those without TH, had lower bowel wall thickness, fat stranding, and Clermont and MaRIA scores but higher ADC levels [ 71 ].…”
Section: Magnetic Resonance Enterographymentioning
confidence: 99%
“…TH was defined as having a bowel wall thickness ≤ 3 mm without any signs of inflammation at week 26. The subgroup of patients who reached TH, compared with those without TH, had lower bowel wall thickness, fat stranding, and Clermont and MaRIA scores but higher ADC levels [ 71 ].…”
Section: Magnetic Resonance Enterographymentioning
confidence: 99%
“…And 11.3% of patients achieved transmural healing at W16, mainly in the colon. The clinical trial of Longyuan Zhou et al[45] found that nearly one-fifth of patients observed early TH assessed by MRE at week 26 of ustekinumab (UST) treatment; The apparent diffusion coefficient (ADC), one of the parameters of MRE evaluated, may positively predict early TH.…”
mentioning
confidence: 99%